Experience of entrepreneurial training for female farmers to stimulate entrepreneurship in Uganda. Issue 7 (30th September 2014) - Lourenço, Fernando; Sappleton, Natalie; Dardaine-Edwards, Akosua; McElwee, Gerard; Cheng, Ranis; W. Taylor, David; G. Taylor, Anthony
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to evaluate the success of a scheme, supported by the Ugandan Agribusiness Initiative Trust, to fund gender and entrepreneurship training for women farmers in the north of Uganda (Gulu District and Lira District). Moreover, this paper reflects upon our experience of delivering training for women farmers and highlights key observations related to women's entrepreneurship in Uganda. Design/methodology/approach – A practitioner-based reflection which shares the experiences of the process of developing and delivering gender and entrepreneurship training for women in Uganda. Findings – Through the experience of running gender and entrepreneurship training for women farmers in Uganda, a series of barriers to female rural entrepreneurs are highlighted: lack of access to credit, gender inequality, poor infrastructure, lack of access to knowledge and education, negative attitudes towards women and few initiatives to facilitate economic and business success. Originality/value – This paper provides reflection of the experience gained from the delivery of training and interaction with women farmers and entrepreneurs in Uganda.